Photocatalytic degradation of tetracycline antibiotic over a flower-like S-doped BiOBr: Performance, mechanism insight and toxicity assessment - Huang, Jianghua; Li, Cunjun; Hao, Huadong; Li, Liang; Zhu, Baikang; Chen, Xianlei; Tao, Hengcong (Frontiers in Nanotechnology, 2022)
A new catalyst of S-BiOBr flower-like morphology was synthesized by simple pyrolysis, and further used for photocatalytic degradation of TC. Phase structure analysis, elemental analysis and micromorphological analysis confirmed that S doping has a reinforcing effect on the polarization between the [Bi2O2S]2+ and [Br2]2- layers and is conducive to interlayer polarization and rapid charge transfer. In addition, its unique petal morphology is more favorable to the adsorption of contaminants on its surface and accelerates the reaction of catalyst surfactant with contaminants. It was also found that S-BiOBr degrades TC significantly better than single BiOBr@HCs, with up to 99.1% in 60 min illumination. In addition, the S-BiOBr catalyst has good reusability in antibiotic degradation. The results of photocatalytic mechanism analysis show that free radical ·O2- plays a major role in the photodegradation of organic model pollutants. Intermediates in TC degradation were identified, and their potential degradation pathways were prospected. The S-BiOBr photocatalytic system developed in this paper provides a new idea for effective modification of bismuth-based semiconductors and has important guiding significance for future water purification.